Gambaran Status Gizi dan Aktivitas Fisik Remaja Selama Pandemi COVID-19 - Charles Leonardo; Dary Dary; Dennys Christovel Dese (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: The covid-19 pandemic that occurred in Indonesia has brought many changes, especially for teenagers, namely the limitations in carrying out activities, online learning, and an appeal to stay at home to prevent the spread of the covid-19 virus. These changes can have various impacts on the nutritional status and physical activity of adolescents. The purpose of this study is to describe the nutritional status and physical activity of adolescents during the covid-19 pandemic.Methods: This research method uses descriptive quantitative research method with a cross-sectional approach. This research was conducted at SMPN 2 Raren Batuah, Unsum Village, Raren Batuah District, East Barito Regency, Central Kalimantan Province in January - March 2021. This sampling technique used total sampling with a total of 91 male and female adolescent respondents with a range of ages 13 - 15 years (early teens). Data collection in this study used anthropometric measurements to measure nutritional status, and the PAQ-C (Physical Activity Questionnaire for Older Children) questionnaire to measure physical activity.Results: The results showed that the nutritional status of adolescents based on BMI/U was in the normal category of 78% and the rest had nutritional problems. While the physical activity of adolescents based on the category that is light activity is 49%.Conclusion: Based on the results of the study, there may be a relationship between nutritional status and physical activity during the covid-19 pandemic.